Plankton Abundance in Senggarang Waters as Blue Swimming Crab Catchment Area, Tanjungpinang City, Riau Islands - Wahyu Muzammil; Nurhidayah Rahmah; Tri Apriadi; Winny Retna Melani; Andi Zulfikar (Institut Pertanian Bogor, 2026)
Senggarang waters are a traditional fishing spot for small-scale blue swimming crab (BSC) fishermen in Tanjungpinang City. The fishermen have their own BSC catchment areas to capture this product, which is the primary aim. Plankton, an aquatic microbe that lives floating in the water column and can't move or only move slightly to follow the current, has a high ecological significance as a source of food for fisheries biota. The purpose of this study was to monitor the existence of plankton by determining plankton abundance, diversity index, uniformity index, and plankton dominance index in crab fishermen's traditional fishing grounds in Senggarang seas. This is a quantitative study; planktons were sampled at 10.00−13.00 using the horizontal static method with a plankton net, placed in a sample bottle, and given 10% Lugol, before being identified at the Marine Biology Laboratory, Faculty of Marine Sciences and Fisheries, Raja Ali Haji Maritime University. Samples were collected for five weeks at five locations designated by purposive sampling in the same location as the BSC fishermen who set their traps (bubu). The results revealed 41 genera of planktons classified as Cyanophyceae, Bacillariophyceae, Branchiopoda, Chlorophyceae, Dinophyceae, Sarcodina, Copepods, and Tintinnidae. The largest plankton abundance occurs in the fourth week of Station 5, with 15961 ind.L−1. The plankton diversity index was low, and the uniformity index was inversely proportional to dominance. Keywords: blue swimming crab catchment areas, plankton abundance, Senggarang Waters, Tanjungpinang City